Eocene magmatism (Maden Complex) in the Southeast Anatolian Orogenic Belt: Magma genesis and tectonic implications - Erturk, Mehmet Ali; Beyarslan, Melahat; Chung, Sun-Lin; Lin, Te-Hsien (China Univ Geosciences, Beijing, 2018)
The origin and geodynamic setting of the Maden Complex, which is situated in the Bitlis-Zagros Suture Zone in the Southeast Anatolian Orogenic Belt, is still controversial due to lack of systematic geological and geochemical data. Here we present new whole rock major-trace-rare earth element and Sr-Nd isotope data from the Middle Eocene volcanic rocks exposed in Maden Complex and discuss their origin in the light of new and old data. The volcanic lithologies are represented mainly by basalt and andesite, and minor dacite that vary from low-K tholeiitic, calc-alkaline, high-K calc-alkaline, and shoshonitic in composition. They exhibit enrichments in large ion lithophile and light rare earth elements, with depletions in high field strength elements. Basaltic rocks have uniform Sr and Nd isotope ratios with high epsilon(Nd)(t) values varying from +5.5 to +6.7, in contrast to, andesitic rocks are characterized by low epsilon(Nd)(t) values ranging from -1.6 to -10. These geochemical and isotopic characteristics indicate that two end-members, a subduction-related mantle source and a continental crust, were involved in the magma genesis. Considering all geological and geochemical data, we suggest that the Eocene Maden magmatism occurred as a post-collisional product by asthenospheric upwelling owing to convective removal of the lithosphere during an extensional collapse of the Southeast Anatolian ranges. (C) 2017, China University of Geosciences (Beijing) and Peking University. Production and hosting by Elsevier B. V.
Keywords: Maden Complex; Eocene magmatism; Southeast Turkey; Asthenospheric upwelling